The Legal Regulation of Electronic Companies - Swidan, Hashem (Milev Journal of Research and Studies, 2022)
Electronic companies are considered one of the prerequisites of the technical revolution in the field of communications and informatics, through which companies aim to provide their services electronically. Traditional companies have taken to convert to electronic companies or create exclusive electronic companies; this is because this form of company has the advantage of saving effort and time. Hence, the importance of this study is to identify the legal regulation of electronic companies in Palestine, which takes place in an intangible environment, and to demonstrate the adequacy of the relevant legal rules for their regulation under the Electronic Transactions Law and the relevant laws, by indicating the meaning of the electronic company, its distinctive characteristics and the procedures for its establishment.